(untitled) (Research, Society and Development, 2020)
The objective was to differentiate dairy farms and correlate their characteristics with the occurrence of Unstable non-acid milk (UNAM) in the far west of Santa Catarina. In addition to ascertaining the lowest graduation in the alcohol test for milk selection in a commercial dairy. Assessments were made at 45 farms that sold milk in the commercial dairy. Management and production characteristics were identified between August and December of 2016. Milk samples were collected biweekly from the cooling tank between August 2016 and July 2017. They were analyzed for stability to alcohol testing in gradations from 72 to 80 % at 2% intervals, in addition to the boil test, titratable acidity, and pH. The Pearson’s Chi-square test was used to evaluate the difference between the UNAM in the graduations tested and the regression analysis to estimate the effect of quantitative variables on the accumulated UNAM. Regression analysis as performed to verify the effect of the month of the year on the UNAM. The milk production in 91% of the farms was in the pasture system with supplementation and the rest in semiconfinement. The area of the farm was 23.6 ± 16 ha to keep 23.6 ± 9.3 lactating cows producing on average of 16.6 ± 4.9 liters/cow. The incidence of UNAM increased concomitantly with the increase in the alcoholic grade used in the test and, in February, the lowest grade for identification of UNAM was found. The study concluded that the accumulated UNAM correlated negatively with the area to produce food and animal productivity. The 76% alcohol content is the best alternative to select commercialized milk.